The use of different oak products during the fermentation and ageing of Chenin Blanc : sensory properties, perceived quality, and consumer preference - Botha, Anri (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.